1996
DOI: 10.1021/jo961003q
|View full text |Cite
|
Sign up to set email alerts
|

Role of the [4.2.2] Bicyclic Unit in Bicyclomycin:  Synthesis, Structure, Chemical, Biochemical, and Biological Properties

Abstract: Twelve bicyclomycin derivatives were synthesized to determine the effect of modification of the [4.2.2] bicyclic unit in bicyclomycin (1) on drug function. Few bicyclomycin derivatives have been described in which the [4.2.2] ring system has been modified. The compounds evaluated were divided into two categories: the two N-methyl-modified bicyclomycins (2, 3) and the ten C(6)-substituted bicyclomycins (4-13). Substituents introduced at the C(6) site included alkoxy, thioalkoxy, thiophenoxy, anilino, and hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 20 publications
(33 reference statements)
2
37
0
Order By: Relevance
“…Aliquots (2 l) were removed at various times (15,30,45, 60, and 75 s) during the reaction and spotted onto polyethyleneimine TLC sheets that had been prerun in water and dried. [␥- 32 P]ATP and 32 P i were separated by chromatography on the polyethyleneimine sheets using 0.75 M KH 2 PO 4 , pH 3.5, as the mobile phase. The developed TLC plates were used to expose PhosphorImager plates (10 -20 min) and scanned using a Fuji BAS 1000 BioImaging Analyzer; the radioactive spots were analyzed using the Macintosh BAS analysis program.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aliquots (2 l) were removed at various times (15,30,45, 60, and 75 s) during the reaction and spotted onto polyethyleneimine TLC sheets that had been prerun in water and dried. [␥- 32 P]ATP and 32 P i were separated by chromatography on the polyethyleneimine sheets using 0.75 M KH 2 PO 4 , pH 3.5, as the mobile phase. The developed TLC plates were used to expose PhosphorImager plates (10 -20 min) and scanned using a Fuji BAS 1000 BioImaging Analyzer; the radioactive spots were analyzed using the Macintosh BAS analysis program.…”
Section: Methodsmentioning
confidence: 99%
“…2 The use of analogues acting as irreversible inactivators has proven to be a useful approach for the identification of substrate-binding sites in enzymes (30). A recent structure-activity relationship study of Bcm (31)(32)(33) has identified 5a-(3-formylanilino)dihydrobicyclomycin (FD-Bcm) as a potential reductive amination probe that warranted further study (34). FD-Bcm has Rho inhibitory properties comparable with Bcm.…”
Section: Bicyclomycin (Bcm)mentioning
confidence: 99%
“…In the first, we determined the structureactivity relationship (SAR) for bicyclomycin inhibition of rho [119][120][121][122][123][124][125][126][127][128][129][130][131]. In the second, we identified key amino acid residues in rho necessary for rho binding [74].…”
Section: Preliminary Studies On the Identi-fication Of The Bicyclomycmentioning
confidence: 99%
“…The second sector modified in 1 was the central bicyclic unit [123,124]. The 11 compounds prepared were divided into two categories: the amide-modified bicyclomycins (A) and the C(6)-substituted bicyclomycins (B) (Fig.…”
Section: The [422] Bicyclic Unitmentioning
confidence: 99%
See 1 more Smart Citation